2013
DOI: 10.1084/jem.20130761
|View full text |Cite
|
Sign up to set email alerts
|

The skin is an important bulwark of acquired immunity against intestinal helminths

Abstract: IL-4–producing basophils promote the trapping of N. brasiliensis in the skin during secondary infection, a process critical for limiting the spread of infection to the lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
156
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(164 citation statements)
references
References 56 publications
(95 reference statements)
4
156
0
Order By: Relevance
“…Arginase 1 produced by M2-type macrophages is involved in the larval trapping in the skin. Depletion of either basophils or M2-type macrophages abolishes the larval trapping in the skin, but it has no significant impact on eosinophil accumulation in the infected skin (36). As shown in Fig.…”
Section: δDblgata Mice Show Impaired Acquired Protection Against Helmmentioning
confidence: 75%
See 2 more Smart Citations
“…Arginase 1 produced by M2-type macrophages is involved in the larval trapping in the skin. Depletion of either basophils or M2-type macrophages abolishes the larval trapping in the skin, but it has no significant impact on eosinophil accumulation in the infected skin (36). As shown in Fig.…”
Section: δDblgata Mice Show Impaired Acquired Protection Against Helmmentioning
confidence: 75%
“…Mice were first injected s.c. with 500 third-stage larvae (L3) of N. brasiliensis in the back, and 18 d later, they were injected intradermally with 500 L3 in the flank. Two days after the second larva inoculation, the skin of the inoculation site was isolated, and subjected to numerical counts of skin-trapped larvae and skin-infiltrating cells as described previously (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that basophils cooperate with dendritic cells to initiate Th2 responses, promote alternative activation of macrophages, and contribute to acquired resistance against parasites (12)(13)(14)(15)(16). We and others have shown that basophils contribute to protective immune responses against secondary infection by Nb and ticks (13,14,17). Antibodymediated depletion of basophils also was reported to result in partially impaired protection against Hp and Trichuris muris (18,19).…”
mentioning
confidence: 87%
“…63 Similarly, female mice are resistant to T. muris infection in the absence of IL-4 (in contrast to their male counterparts) mostly because of a stronger propensity for IL-13 production. 66 Furthermore, with the exception of IL-4 in the skin, 67 IL-4 appears to be dispensable for N. brasiliensis expulsion. 61,68 The redundancy between IL-4 and IL-13 likely stems from their shared usage of the IL-4Ra subunit, [69][70][71] although interestingly, IL-4Ra deficiency in T cells has no impact on worm expulsion during either T. spiralis, 72 H. polygyrus, 73 or N. brasiliensis 61,62 infections, in contrast to total IL-4Ra ablation.…”
Section: Transmissionmentioning
confidence: 99%